A systems engineering approach to variable intakes for civil aviation. (August 2020) - Kazula, Stefan; Höschler, Klaus
A systems engineering approach to develop variable nacelle intakes for aero engines in civil aviation is presented. The goal of this methodical approach is to find solutions to design problems that can be successfully utilised in aviation without further effort during the certification. By using variable intakes, aircraft and aero engine manufacturers can fulfil their customers' needs for safe, efficient and fast travelling. Therefore, a system shall be installed which is able to modify the nacelle intake contour between two extrema. On the one hand, a sharp thin contour, which produces low drag and allows to fly faster or more efficiently, is optimal during cruise condition. On the other hand, a round thick intake lip is necessary to avoid flow separations with the potential to cause dangerous events during take-off and climb conditions. The utilised systems engineering approach is introduced. The executed steps and methods used for creating and evaluating concept variants for variable intakes are displayed particularly. Those contain the determination and evaluation of requirements and functions as well as the generation and assessment of concepts. Finally, yet importantly, following tasks are presented.